New insights into neutrophil and Leishmania infantum in vitro immune interactions. (June 2015) - Marques, Cláudia S.; Passero, Luiz Felipe D.; Vale-Gato, Inês; Rodrigues, Armanda; Rodrigues, Olivia Roos; Martins, Catarina; Correia, Ivone; Tomás, Ana M.; Alexandre-Pires, Graça; Ferronha, M. Helena; Santos-Gomes, Gabriela M.
Abstract: The interaction between polymorphonuclear leukocytes (PMN) or neutrophils and Leishmania became an interesting focus of research, since PMN turn out to be essential cells in transiently hosting the parasites. This study aims to evaluate whether L. infantum, the etiological agent of zoonotic visceral leishmaniasis, influences the in vitro functional activity of murine neutrophils. Phagocytosis, chemotaxis, oxidative burst, degranulation and apoptosis assays were performed. Cytokines, chemokines and toll-like receptors gene expression were evaluated by Real-time PCR. Results indicate that some of the innate features of PMN immunity were activated when in contact with L. infantum. However, parasites might negatively interfere with PMN defense mechanisms compromising the link between innate and acquired immunity. This work provides additional insights on the inflammatory immune interactions between neutrophils and L. infantum highlighting the role of PMN in Leishmania infection.